2019
DOI: 10.3390/app9163250
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces Cerevisiae Var. Boulardii: Valuable Probiotic Starter for Craft Beer Production

Abstract: The use of probiotic starters remaining viable in unpasteurized and unfiltered beers could significantly increase health benefits. Here, the probiotic Saccharomyces cerevisiae var. boulardii (Sc b ) and a commercial Saccharomyces cerevisiae (Sc) strain, which is commonly employed in the brewing industry, are compared as single starters. The healthy value of the produced beers and growth performance in a laboratory bioreactor are analysed by determining antioxidant activity, phenolic content and profile, alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 69 publications
6
26
0
6
Order By: Relevance
“…The obtained product has similar sensory qualities with the traditional product, high commercial characteristics, and lower value of pH, which helps to maintain the beer's shelf life [88]. It has also been described by Mulero-Cerezo et al (2019) that Saccharomyces boulardii show higher viability during the fermentation process, which is ideal for producing a craft beer containing viable probiotic cells [34]. Several studies demonstrated that Saccharomyces boulardii can generate bioactive compounds in fermented beverages thus improving their functionality [89,90].…”
Section: New Trends Regarding Yeasts Involved In Fermentation Of Specmentioning
confidence: 66%
See 1 more Smart Citation
“…The obtained product has similar sensory qualities with the traditional product, high commercial characteristics, and lower value of pH, which helps to maintain the beer's shelf life [88]. It has also been described by Mulero-Cerezo et al (2019) that Saccharomyces boulardii show higher viability during the fermentation process, which is ideal for producing a craft beer containing viable probiotic cells [34]. Several studies demonstrated that Saccharomyces boulardii can generate bioactive compounds in fermented beverages thus improving their functionality [89,90].…”
Section: New Trends Regarding Yeasts Involved In Fermentation Of Specmentioning
confidence: 66%
“…Over the past decade, there has been a global rise in the consumer interest in craft beers (CBs), particularly in traditional ales, and lagers, which are distinctively flavored, have a unique quality value and overall particular sensory properties [15]. Besides CBs are produced locally, in small quantities, are unpasteurized, unfiltered, and without added nitrogen or carbon dioxide pressure [34]. There are three major categories of brewers making CB and these are brewpubs, microbreweries, and regional craft breweries [35].…”
Section: Introductionmentioning
confidence: 99%
“…Mulero-Cerezo et al, reported that "Saccharomyces cerevisiae var. boulardii as a single yeast starter produces craft beer with higher antioxidant activity, lower alcohol content, similar sensory attributes and higher yeast viability after 45 days than that produced by a commercial Saccharomyces cerevisiae strain commonly used in the brewery industry" [56]. The results published by de Paula et al, also show that functional beer containing S. cerevisiae var.…”
Section: Probiotic and Potentially Probiotic Yeasts In The Aspect Of Functional Foodmentioning
confidence: 96%
“…In recent studies, S. boulardii has had suitable resistance to alcohol and gastrointestinal conditions for probiotic alcoholic beverage development [140]. The use of S. boulardii as a mixed starter with S. cerevisiae for craft beer, or as single starter for alcohol-free beer production has been proposed recently [141][142][143]. In other studies, S. boulardii, used as a single yeast starter culture for brewing, has been shown to produce craft beer with higher antioxidant activity, lower alcohol content, and similar sensory attributes as the craft beer obtained with S. cerevisiae strains.…”
Section: Probiotic Beermentioning
confidence: 99%